Efek Mediasi Affective Commitment antara Pengaruh Job Embeddedness terhadap Turnover Intention - Nana Nabella, Annisa (Jurnal Ilmu Manajemen, 2021)
The high turnover intention is a serious problem in various companies. It leads to an extraordinary misuse of assets and increases management costs. The turnover intention in employees could be explained from the micro (psychological) and macro (organizational and economic) sides. This research aimed to investigate and analyze job embeddedness and affective commitment on employees’ turnover intention. This research uses a quantitative methodology to conduct a causality investigation. The survey of 85 employees was conducted in Mega Elektronik Nganjuk. The data were analyzed by PLS-SEM with SmartPLS (v.3.3.3). The study’s findings put into words that job embeddedness has a negative and significant influence on turnover intention. Off the job embeddedness has no significant influence on turnover intention. On the job embeddedness has a positive and significant influence on affective commitment. Off the job embeddedness has a positive and significant influence on affective commitment. Affective commitment has a negative and significant influence on turnover intention. Affective commitment partially mediated the relationship between the job embeddedness and turnover intention. Affective commitment fully mediated the relationship between off the job embeddedness and turnover intention. The implication of this study is that the company should pay attention to employees who want to leave the company with good communication so the obstacles in work can be conveyed and get the best solution.